2020
DOI: 10.1101/2020.04.20.049106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studies on CRMP2 SUMOylation-deficient transgenic mice identify sex-specific NaV1.7 regulation in the pathogenesis of chronic neuropathic pain

Abstract: The sodium channel NaV1.7 is a master regulator of nociceptive neuronal firing. Mutations in this channel can result in painful conditions as well as produce insensitivity to pain. Despite being recognized as a "poster child" for nociceptive signaling and human pain, targeting NaV1.7 has not yet produced a clinical drug. Recent work has illuminated the NaV1.7 interactome, offering insights into the regulation of these channels and identifying potentially new druggable targets. Amongst the regulators of NaV1.7 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(43 citation statements)
references
References 70 publications
8
35
0
Order By: Relevance
“…In contrast, none of these effects were observed in male mice, suggesting that the CRMP2 K374A/K374A mutation imposed a sexspecific regulation on NaV1.7. Of relevance to the role of NaV1.7 in pain, we found that CRMP2 K374A/K374A mice of both sexes failed to develop mechanical allodynia after a spinal nerve injury (SNI) (28), thus supporting the conclusion that CRMP2 SUMOylation-dependent regulation of NaV1.7 still holds in chronic neuropathic pain in male mice. Together, these studies underscore the critical role of CRMP2 SUMOylation as a regulatory mechanism underlying NaV1.7 functional expression.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…In contrast, none of these effects were observed in male mice, suggesting that the CRMP2 K374A/K374A mutation imposed a sexspecific regulation on NaV1.7. Of relevance to the role of NaV1.7 in pain, we found that CRMP2 K374A/K374A mice of both sexes failed to develop mechanical allodynia after a spinal nerve injury (SNI) (28), thus supporting the conclusion that CRMP2 SUMOylation-dependent regulation of NaV1.7 still holds in chronic neuropathic pain in male mice. Together, these studies underscore the critical role of CRMP2 SUMOylation as a regulatory mechanism underlying NaV1.7 functional expression.…”
Section: Introductionsupporting
confidence: 57%
“…Although CRMP2 SUMOylation was abolished in both male and female homozygous mice, we unexpectedly discovered that CRMP2 dependent NaV1.7 trafficking was sexually dimorphic (28). In female mice only, germline loss of CRMP2 SUMOylation reduced NaV1.7-CRMP2 binding, NaV1.7 membrane localization and NaV1.7 currents in DRG sensory neurons, compared to their wildtype (WT) littermates (28). Inhibiting clathrin assembly with Pitstop2 (29), rescued the decreased sodium currents back to the levels observed in DRG from WT female mice.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations